Improving History Learning Outcomes Through Project-Based Learning (PjBL) with a Cultural Approach (CRT) in Class XII MIA 3 SMA Negeri 3 Medan - Sarumaha, Margaretha Tania; Nugraha, Muhammad Adika; Sihotang, Masniar (LPPPI Publishing, 2024)
Improving learning outcomes is the goal of this classroom action research, student learning outcomes in history learning through Project Based Learning (PjBL) model with a Cultural Approach (CRT) in class XII MIA 3 SMA Negeri 3 Medan. This research is a type of classroom action research (PTK) with qualitative descriptive analysis techniques. This research was at SMA Negeri 3 Medan. Class XII MIA 3 students, totaling 36 students, were the subjects of this research. This research was carried out in two cycles, while the data collection techniques used were observation, tests and document review. The research results seen that through the application of Project Based Learning with a Cultural Approach it can improve the learning outcomes of class XII MIA 3 students at SMA Negeri 3 Medan. This increase is proven through the presentation of learning outcomes in class which has increased, namely pre-cycle 41.66%, cycle 1 66.66% and cycle 2 86.11%. This means that it can be concluded that based on the results of the percentage of graduates who achieved a learning outcome score of more than KKM = 75 in cycle 2 = 86.11%, the Project Based Learning model with a Cultural Approach is said to be successful.